2016
DOI: 10.1016/j.econmod.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Business cycle synchronisation in EMU: Can fiscal policy bring member-countries closer?

Abstract: The present study adds to the literature on the impact of fiscal policy on business cycle synchronisation. Specifically, it investigates the effects of fiscal policy on business cycle synchronisation between the 10 EMU member-countries and the aggregate EMU12-wide business cycle, using a time-varying framework. The findings suggest that fiscal policy has important effects on business cycle synchronisation for all 10 EMU countries. Hence, fiscal policy is shown to have the potential to be supportive of macroeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 66 publications
1
18
2
Order By: Relevance
“…Put simply, these findings suggest that deviations in country‐specific fiscal policy stances tend to promote higher synchronization, which is in line with the policy prescription associated with OCA theory. Similar findings have also been shown by Degiannakis et al (). In contrast, Böwer and Guillemineau () find that fiscal policy differentials have driven differences between countries’ business cycles only prior to the establishment of the Stability and Growth Pact.…”
Section: The Determinants Of Time‐varying Business Cycle Synchronizationcontrasting
confidence: 86%
See 4 more Smart Citations
“…Put simply, these findings suggest that deviations in country‐specific fiscal policy stances tend to promote higher synchronization, which is in line with the policy prescription associated with OCA theory. Similar findings have also been shown by Degiannakis et al (). In contrast, Böwer and Guillemineau () find that fiscal policy differentials have driven differences between countries’ business cycles only prior to the establishment of the Stability and Growth Pact.…”
Section: The Determinants Of Time‐varying Business Cycle Synchronizationcontrasting
confidence: 86%
“…Dynamic business cycle synchronization (BCS ij,t ) can be approximated by the time‐varying correlation level between two countries’ cyclical components. Recent studies in this strand of the literature have shown that multivariate GARCH models, such as the Baba, Engle, Kraft and Kroner (BEKK) model of Engle and Kroner () are successful in capturing the time‐varying synchronization, as this is approximated by the dynamic correlations (see, Degiannakis et al, ; Degiannakis et al, ). Given the low frequency of our data, and the relatively small time period, we use a more parsimonious version of the BEKK model, namely the Diagonal BEKK (Diag‐BEKK) model, as used by Degiannakis et al ().…”
Section: Data and Methods Descriptionmentioning
confidence: 99%
See 3 more Smart Citations